Diagnostic value of electroanatomical mapping in patients with suspected arrhythmogenic cardiomyopathy. (3rd October 2022) - Berg, J; Villatore, A; Sivilotti, F; Pili, G; Sala, S; Della Bella, P; Peretto, G
Abstract: Background: Case series suggested that low voltage areas (LVA) on invasive electroanatomical mapping (EAM) could identify arrhythmogenic cardiomyopathy (ACM) at an earlier stage as compared to late gadolinium enhancement (LGE) and fatty infiltration on cardiac magnetic resonance (CMR). Data comparing LVA with structural abnormalities on CMR are lacking. Purpose: To report the prevalence of substrate abnormalities identified by EAM vs. CMR in a cohort of patients with suspected ACM. Methods: We retrospectively identified 66 consecutive patients with suspected ACM, who underwent EAM following clinical onset with ventricular arrhythmias. The cutoff value for EAM-defined LVA was <0.5 mV bipolar, <8 mV unipolar. Data from a prior CMR, performed no more than 12 months before, were used for comparison. Results: The study cohort (mean age 47 years, range 21–76; 83% males; mean left ventricular ejection fraction 53%, range 28–70%) was composed of patients with suspected ACM involving either the right (n=62) or the left ventricle (n=4) following presentation with sustained monomorphic ventricular tachycardia. EAM was obtained by isolated endocardial, epicardial, or combined approach, respectively, in 11 (17%), 15 (23%) and 40 (61%) patients. Overall, 61 patients (92%) had documented LVA, of whom 89% showed an epicardial localization. In the same population, CMR identified a lower prevalence of substrate abnormalities (LGE 65%; fatty infiltration 50%). In particular, there were 27 patients (41%) with EAM-defined LVA and absent substrate abnormalities on CMR. Based on the 2010 Task Force Criteria and the 2021 Padua Criteria, a definite diagnosis of ACM was missing for a total of 19 patients (29%): due to the uniform identification of LVA in the absence of CMR abnormalities, EAM helped to establish the most likely diagnosis of ACM in all of them (19/19). Conclusions: Our data suggest that EAM is capable of identifying substrate abnormalities in a consistent proportion of patients with suspected ACM and absent abnormalities on CMR. In this setting, the implementation of LVA to the current diagnostic criteria could improve the diagnostic yield for ACM. Funding Acknowledgement: Type of funding sources: None.